2016
DOI: 10.1007/s00436-016-5288-7
|View full text |Cite
|
Sign up to set email alerts
|

Sarcocystis entzerothi n. sp. from the European roe deer (Capreolus capreolus)

Abstract: In the present study, we describe Sarcocystis entzerothi n. sp. from the European roe deer (Capreolus capreolus) based on the microscopical and DNA analysis. By light microscopy (LM), cysts of S. entzerothi were spindle-shaped with pointed tips, 950-1900 × 70-150 μm in size and had 5-6 μm long finger-like cyst wall protrusions. Cyst wall of S. entzerothi by transmission electron microscopy (TEM) was type 10a-like; villar protrusions were up to 1.2 μm wide, densely packed, lying about 0.1 μm between each other,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…from cattle have been molecularly characterised at the genes for 18S rRNA (18S rRNA), 28S rRNA (28S rRNA) and cytochrome c oxidase subunit I (cox1) and at nuclear rDNA internal transcribed spacer 1 (ITS1) [8,10,11,15]. Databases contain many 18S rRNA gene sequences of the genus Sarcocystis used for species identification [16][17][18]. However, studies have revealed that cox1 is the preferable target to differentiate taxonomically related Sarcocystis spp.…”
mentioning
confidence: 99%
“…from cattle have been molecularly characterised at the genes for 18S rRNA (18S rRNA), 28S rRNA (28S rRNA) and cytochrome c oxidase subunit I (cox1) and at nuclear rDNA internal transcribed spacer 1 (ITS1) [8,10,11,15]. Databases contain many 18S rRNA gene sequences of the genus Sarcocystis used for species identification [16][17][18]. However, studies have revealed that cox1 is the preferable target to differentiate taxonomically related Sarcocystis spp.…”
mentioning
confidence: 99%
“…The sarcocysts of S. matsuoae possessed slender finger-like protrusions (Fig. 2f) similar to those of S. entzerothi (Prakas et al, 2017). The size of their sarcocysts were also nearly the same, being 1115 × 112 μm in S. matsuoae (Table 3) and 1139 × 108 μm in S. entzerothi (Prakas et al, 2017).…”
Section: Discussionmentioning
confidence: 82%
“…Hence, this cyst type may not be as prevalent as suggested by its repeated reporting, and the sarcocysts examined by LM or SEM in some of these studies might belong to a different species. The finger-like cyst-wall protrusions of the single cyst depicted in the TEM micrographs in these papers seem to have a broad round base and a thinner, more flattened distal end, causing the tip of the protrusions to bend over, which are features known from sarcocysts of S. entzerothi (Prakas et al, 2017), Sarcocystis bovifelis , Sarcocystis bovini and Sarcocystis sinensis (Gjerde, 2016a), whereas sarcocysts of S. tarandi have erect columnar/cylindrical protrusions (Gjerde, 1985). Moreover, since S. matsuoae was placed as a sister species to S. entzerothi , it seems likely that the sarcocyst depicted in the abovementioned TEM micrographs belong to S. matsuoae .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations